A Promising Research Ground: Translation Historiography in Brazil - Wyler, Lia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn Brazil, studies in Translation History began in the late eighties and expanded to the extent that by 1998 they had become an area per se in translation fori. The theories by Lefevere, Toury and Holmes are being applied to large corpuses of translations produced from the forties to the seventies in an effort to disclose publishing practices affecting the translation of fiction and the formation of a readership for this genre. New trends in the field include the pooling of human resources to deal with larger projects and an interest in how market demands affect the work of translators.